2007
DOI: 10.1369/jhc.7a7235.2007
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cortactin and Fascin-1 Expression in Gastric Adenocarcinoma: Correlation With Clinicopathological Parameters

Abstract: Cortactin and fascin-1 are important factors in tumor progression. We tested the hypothesis that cortactin and fascin-1 expression correlates with clinicopathological parameters of gastric adenocarcinoma. Immunohistochemical analysis of cortactin and fascin-1 was done using tissue microarrays of 100 surgical specimens, including 20 well-differentiated, 20 moderately differentiated, and 60 poorly differentiated gastric adenocarcinomas. Among the 20 well-differentiated gastric adenocarcinomas, 15 cases (75%) sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 35 publications
5
54
1
Order By: Relevance
“…Cortactin overexpression is known to be associated with the development of cancer (7)(8)(9)(10)(11). The overexpression of cortactin obtained by immunohistochemistry in 62.5% cases of colorectal cancer is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cortactin overexpression is known to be associated with the development of cancer (7)(8)(9)(10)(11). The overexpression of cortactin obtained by immunohistochemistry in 62.5% cases of colorectal cancer is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 89%
“…The C-terminal half is composed of an ·-helix domain of unknown function, followed by a proline-serine-threonine-rich region (PST) and Src homology 3 (SH3) domain (6). Gene amplification of CTTN and overexpression of cortactin have been reported in various cancers including colorectal cancer (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the deregulation of FSCN1 has been reported in gastric cancer. Tsai et al (18) revealed that among 60 samples of poorly-differentiated gastric adenocarcinomas, over half exhibited moderate or marked FSCN1 expression. Notably, a higher expression of FSCN1 correlated directly with more-advanced cancer stages and inversely with survival rates, suggesting that aberrant upregulation of FSCN1 may be involved in the progression of gastric adenocarcinomas.…”
Section: A B Cmentioning
confidence: 99%
“…In addition, the gene's expression was raised significantly at more progressed stages of cancer. In agreement with this study's results, Tsai et al investigated the correlation of cortactin expression with gastric adenocarcinoma clinical parameters through immunohistochemical and tissue microarray analysis [26]. They determined that cortactin overexpression had a direct relationship with more progressed stages of that cancer.…”
Section: Discussionsupporting
confidence: 76%